2017
DOI: 10.21767/2171-6625.1000206
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Trends in Age of First-Ever or Recurrent Stroke in A Rapidly Developing Urban Area during 19 Years

Abstract: Background: To evaluate the trends in age of stroke and compare with recent national wide data in a rapidly developing urban area over the 19 years from 1997 to 2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…8 A study conducted in Korea likewise demonstrated a recurrence incidence of 64% for non-hemorrhagic strokes. 9 In Indonesia, the occurrence rate of repeated stroke is 62%, with 46.8% of these cases being recurrent non-hemorrhagic strokes. According to multiple studies, the occurrence of recurring stroke is significantly elevated, with rates ranging from 25% to 60%.…”
mentioning
confidence: 99%
“…8 A study conducted in Korea likewise demonstrated a recurrence incidence of 64% for non-hemorrhagic strokes. 9 In Indonesia, the occurrence rate of repeated stroke is 62%, with 46.8% of these cases being recurrent non-hemorrhagic strokes. According to multiple studies, the occurrence of recurring stroke is significantly elevated, with rates ranging from 25% to 60%.…”
mentioning
confidence: 99%